Arsenic adsorption and desorption by drinking water treatment residuals: incubation studies - Vandanapu, Vandana; Sarkar, Dibyendu; Datta, Rupali K.; Makris, Konstantinos C. (My University, 2005)
Arsenic (As) has been used for a long time in agricultural practices, primarily to control pests and noxious weeds. In many cases, the indiscriminate usage of toxic arsenical compounds has left a legacy of contaminated soils. Recent awareness of the toxicity of As at much lower concentrations than previously deemed to be dangerous has led to increased interest in the environmental chemistry of As. The immediate challenge, as perceived by various regulatory bodies is to develop a cost-effective, reliable and environmentally sound approach to cleaning up such contaminated soils. In-situ immobilization technologies are an attractive alternative to conventional remediation methods. One of the most interesting of these in-situ techniques is the use of Water Treatment Residuals (WTRs). The WTRs are by-products of drinking water purification processes and generally contain sediments, organic carbon, and Al/Fe oxides. The oxides are typically amorphous (with very high specific surface area) and have tremendous affinity for oxyanions (e.g., arsenate), due to their high positive surface charge. Recent studies conducted by our group have suggested that WTRs retain As and decrease arsenic mobility. However, a better understanding of As adsorption/desorption by WTRs is necessary for effective implementation of appropriate in-situ remedial strategies. Hence, the present study examines the potential use of WTRs (Al-WTR and Fe-WTR) as adsorbents for the removal of arsenate in solutions. Furthermore, it investigates the extent of desorption of the pre-adsorbed arsenate onto the WTR surfaces. Effects of various key parameters, such as solid solution ratio, equilibration time and arsenic concentration were examined to achieve the optimized conditions for arsenate adsorption. Preliminary batch adsorption experiments showed the optimum equilibration time to be 24 h and the solid/solution ratio to be 1:5 for arsenate adsorption. Sorption data has been evaluated using both Langmuir and Freundlich adsorption models; however, the regression coefficients (at 95% confidence interval) demonstrate that the Freundlich model provides better fit to the experimental data in the majority of the cases. Following adsorption, arsenate desorption was investigated using 7500 mg/kg phosphate. A significant amount of As (99%) remained bound to the WTRs even though the phosphate load was equal to the maximum initial As load (7500 mg/kg). This indicates that adsorption of As on WTRs is typically irreversible and, therefore, the WTRs are good prospects for in-situ As fixation. Keywords: Arsenate, water treatment residuals, adsorption, desorption, phosphate.
Keywords: Biogeosciences; Anthropogenic effects; Geochemistry; Pollution; Trace elements